Evaluation of the Influence of Household Behavior, Waste Segregation Practices, and Community Participation on Waste Reduction in Cimahi City - Melawati, Fitri (Westscience Press, 2025)
This study evaluates the influence of household behavior, waste segregation practices, and community participation on waste reduction in Cimahi City. Employing a quantitative approach, data were collected from 200 respondents using a Likert-scale questionnaire and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that all three factors positively and significantly impact waste reduction, with waste segregation practices exerting the strongest influence. Household behavior and community participation also contribute substantially, underscoring their role in sustainable waste management. The model demonstrates substantial explanatory power (R² = 0.65) and predictive relevance (Q² = 0.48). These results highlight the importance of an integrated approach to waste reduction, emphasizing behavioral change, community engagement, and systematic waste segregation to achieve long-term environmental sustainability.